Comparative Study on The Effectiveness of Building Maintenance Scheduling Between Two Multipurpose Hall Buildings - Muhammad Mahathir Shukur; Syed Burhanuddin Hilmi (Recent Trends in Civil Engineering and Built Environment, 2021)
Buildings maintenance is very important for the building and building occupants. Maintenance is a service to make sure the performance of the building in good condition throughout its design life. It is very much needed so we can have very good environment that can help us do our work peacefully. Occupants demand to have priority in terms of comfort of ability to use and utilise the facilities and services as it must be fit for purpose of the user. Work productivity of workers may be demotivated and interrupted due to poor building facilities conditions. In order to prevent that, we have to make sure the building maintenance scheduling are well prepared and followed. This study is about comparative study on the effectiveness of building maintenance scheduling between two multipurpose hall buildings. The objectives of the case study are to investigate the procedure of building maintenance scheduling for the buildings, compare the maintenance scheduling approach between the two multipurpose hall buildings and suggest the best method to practice in the development of building maintenance. This investigation will be carried out through field study and interview from both building. At the end of this study, the data for analysis from the interview have been gathered and it shows that both building are using the same maintenance approaches. Discussion has been explained to provide the comparison for the effectiveness of building maintenance scheduling for both building. Both buildings had made improvement in the building to overcome the building defects and increase the building performance. The buildings have been properly maintain in order to keep it well perform. Some recommendations have been suggested for the future used in having effective building maintenance scheduling. The results from this study are the effectiveness of building maintenance scheduling for both multipurpose buildings have been properly studied and investigated.